Caracterização mecânica e térmica de compósitos de poli (cloreto de vinila) reforçados com fibras de sisal - Martins, Gilson S.; Iozzi, Marco A.; Martins, Maria A.; Mattoso, Luiz H. C.; Ferreira, Fábio C. [UNESP] (Associação Brasileira de Polímeros, 2004)
Compósitos de PVC, plastificados com diferentes sistemas de plastificação e reforçados com fibras de sisal, foram processados em moinho de dois rolos. A influência do tipo e teor do plastificante, do comprimento e do teor das fibras nas propriedades dos compósitos obtidos foi estudada. Dois tipos de plastificantes foram usados, um líquido (do tipo poliéster) e um sólido permanente (copolímero etileno/ acetato de vinila/ monóxido de carbono). As fibras usadas foram previamente lavadas com água a 80 °C por uma hora. Os compósitos, com fibras curtas aleatoriamente distribuídas, foram caracterizados através de ensaio mecânico de resistência à tração, microscopia eletrônica de varredura (MEV), e análises térmicas de calorimetria exploratória diferencial (DSC) e análise por termogravimetria (TG). O comprimento ótimo de fibra obtido para os compósitos foi de 6 mm. O uso do plastificante sólido mostrou-se viável e promoveu uma maior molhabilidade da fibra pela matriz nos compósitos, principalmente para teores acima de 40 pcr. As análises térmicas mostraram que a substituição do plastificante líquido pelo plastificante sólido não afetou a estabilidade térmica das matrizes e dos compósitos.

Composites consisting of flexible polyvinyl chloride (PVC), plasticized with two different types of plasticizers and reinforced with sisal fibers, were processed on a two-roll mixing mill. Two plasticizers were used, a liquid plasticizer (polyester) and a permanent solid plasticizer (ethylene/ vinyl acetate/ carbon monoxide copolymer - Elvaloy® ), to form two kinds of polymeric matrices. For each one of these matrices, the influence of plasticizers type, plasticizers content, size and quantity of sisal fibers in the composite properties has been studied. The fibers were washed with water at 80 °C during one hour. The composites with randomly distributed short fibers were characterized by mechanical analysis, scanning electron microscopy, thermogravimetric analysis (TG) and differential scanning calorimetry (DSC). For each one of the polymeric matrices studied, the optimal size of sisal fiber was 6mm in order to have a better reinforcement, under the conditions investigated. The use of a solid plasticizer was feasible for PVC compositions and promoted a better fiber-matrix contact on the composites, increasing mechanical properties for plasticizer quantity over 40 phr, compared to the liquid plasticizer. Thermal analysis (TG and DSC) demonstrated that the replacement of the liquid by the solid plasticizer does not change the thermal behavior of the composites and unloaded polymeric matrices. For both matrices the elastic modulus is increased as the sisal fibers are added, when compared to unloaded matrices.
Mechanical and thermal characterization of the polyvinyl chloride-sisal fibers composites
Keywords: PVC; plastificante; fibra de sisal; compósitos; Poly (vinyl chloride); plasticizer; sisal fiber; composite